PENYELENGGARAAN GOOD GOVERNANCE DI DESA SEA KECAMATAN PINELENG KABUPATEN MINAHASA - RUATA, YUNITA; POSUMAH, JOHNNY HANNY; MAMBO, RULLY (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACTThis research there are problems in implementing Good Governance at the village of Sea, have not gone wellaccording law No. 8 of 1999 on the implementation of good governance. The researchers used a qualitative researchmethod. The data was collected starting from the stage of observation, in-depth interviews and documentation. Onthe data collection was completed by using the guidelines of the interview, where there are 10 informantsinterviewed.After being interviewed, the researchers analyzed the results of interviews with several phases. The first of themwith the data collection was done through observation or interviews, then do record keeping and typing and editingas necessary, both the reduction i.e. elections against existing data, sharpen data analysis, summarize and discarddata that is not needed, the third provides data and simplifying data have been obtained in order to facilitate researchin the conclusion, the fourth withdrawal i.e., verify their conclusions with a review the records or data retrieved aswell as analyze causal including brainstorm with friends and supervising professors and take conclusion.The results showed that organizing Good Governance have not applied optimally as expected by law No. 8 in 1999and the theory of Inu Kencana, 1994.The conclusion that can be drawn through the results of this research is that found there are some principles of GoodGovernance that has not gone well. Of which public participation is still very lacking in the process management ofthe KTP & KK, law enforcement has been running fine but for the better should the existence of PERDES,transparency needs to be improved in terms of disclosure for financial management to the community. Responsifitasthe Government is still lacking in terms of service the rice still need for renewing the data community who deservethe rice, RKPdesa village and Profile updates need to be made in accordance with the year 2016, the lack of aGovernment response, information boards, still less to embrace the community in order to make KK and ID CARD.Consensus is already well underway, however, Equality with regard to note what's special in service of rice, theGovernment should give the rights of the underprivileged community, lest not right on target, effectiveness andefficiency can not be rated good because there are problems that have been described above so that the communitycan be felt yet. Accountability has been running good since the village was already running task for reporting to theDistrict about financial management and already inform the community about the program that will be implemented.With this research is expected to be the subject of study of the theory of society and contribute as well as input forthe Government in realizing Good Governance effectively and efficiently.Key Words: Good Governance